MAKING SENSE OF THE WORLD: AN INTERVIEW WITH DAVID KRANTZ - Jhon Shooter (Buletin Psikologi, 1993)
David L. Krantz is Professor of Psychology at Lake Forest College. A Fromer Fellow at the Center for Advanced Studies in Behavioral Science, be has published articles and books in the social psychology of science and topic related to power, knowing, and life's meaning. He recently completed a book tentatively titled journays and Destinations: Searching for life's Meanings while a Visiting Professor at the University of Ghent, Belgium.